Performance evaluation of decode‐and‐forward‐based asymmetric SIMO‐RF/FSO system with misalignment errors. Issue 14 (27th September 2017) - Singhal, Neha; Bansal, Ankur; Kumar, Ashwni
Abstract : The authors analyse a dual‐hop mixed radio frequency/free space optical (RF/FSO) communication system comprising of single‐input multiple‐output (SIMO) RF hop and a single FSO hop. The RF source is connected to an optical destination through a decode‐and‐forward relay having RF/FSO capabilities. Each link in SIMO‐RF hop is assumed to experience independent and identically distributed (i.i.d.) Nakagami‐ m fading. For FSO hop, a unified novel expression for the probability density function (PDF) of irradiance has been derived which unifies Gamma–Gamma and generalised‐ K ( K G ) distributions with misalignment error. Moreover, we obtain a unified PDF of instantaneous signal‐to‐noise ratio (SNR) by unifying the heterodyne detection and intensity modulation/direct detection schemes. Utilising the unified PDF, we derive novel unified closed‐form expressions for average symbol error probability (for different RF modulation techniques), outage probability, and ergodic capacity for the system under consideration. We have also analysed the considered system for high SNR conditions and have analytically obtained the unified diversity order of the same. The derived results clearly show the impact of misalignment error, severe atmospheric conditions, type of detection scheme, and number of RF links on the system performance. All the analytical results are validated through simulations.